Exploring the gem-dimethyl effect in the formation of imine-based macrocycles and cages - Madhu, Suresh; Rashmi, E. V.; Gonnade, Rajesh Ghanshyam; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2017)
Using the gem-dimethyl effect as a platform, a variety of organic [2+2] macrocycles and [2+3] cofacial cages was obtained in high yields. Imine-based macrocyclization could be performed even at high concentrations (0.5 to 1.0 M), via instant mixing of aldehydes and amines.

Three-dimensional metal-organic polymer of multivalent hexaphenylbenzene - Madhu, Suresh; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (ChemistrySelect, 2018)
Metal-Organic Frameworks(MOFs) synthesized from ligands more than ten co-ordinating sites may offer material applications due to their structural architecture. Herein, a synthesis of metal-organic framework is reported from a ligand featuring 12-aryl carboxylic acid groups appended on a hexaphenylbenzene and s-block element potassium. The synthesized MOF was characterized by thermogravimetric analysis, infrared spectroscopy and X-diffraction studies. The X-ray crystal structure of MOF was shown to have a significant number of trapped and coordinated water molecules in its three-dimensional framework.

Twelve-armed hexaphenylbenzene-based giant supramolecular framework for entrapping guest molecules - Madhu, Suresh; Gonnade, Rajesh G.; Das, Tamal; Vanka, Kumar; Sanjayan, Gangadhar J. (ChemPlusChem, 2018)
Host-guest chemistry is a functional model in supramolecular chemistry for understanding specific process occurring in biological systems. Herein, we describe a rationally designed giant multiarmed hexaphenylbenzene (HPB)-based supramolecular frameworks which encapsulate a variety of guest molecules in the voids of their crystal lattice through the cooperative interplay of multivalency, noncovalent forces and backbone rigidity. In this connection, pseudo-axially substituted twelve-armed hexaphenylbenzene was synthesized and its molecular entrapping nature was studied by varying number of H-bond donor-acceptor sites in the arms. The per-methyl esterified HPB acted as a cavitand to include nonpolar and polar aprotic guests in its crystal structure via C-H center dot center dot center dot pi, C-H center dot center dot center dot O and C-H center dot center dot center dot N interactions. The corresponding amidated HPB showed unprecedented inclusion of ammonia and segregation of the guest molecules according to their polarity in the lattice. Furthermore, this molecular entrapping system has been used to obtain the crystal structure of a hitherto unproven 2-azaallenium intermediate, which had been proposed to be involved in aminomethylation of activated arenes.

Dimedone-based rigid organic scaffold for organizing symmetrical helical peptide chains. - Madica, Krishnaprasad; Lakshmi, Jerripothula K.; Madhu, Suresh; Nadimpally, Krishna Chaitanya; Gonnade, Rajesh; Jagadeesh, Bharatam; Sanjayan, Gangadhar J. (ChemistrySelect, 2019)
We describe herein design, synthesis and conformational investigations of polypeptides attached on a rigid dimedone template. Two identical peptide chains are attached on a single carbon containing dimedone as a scaffold. Dimedone assists in controlling the secondary interactions through strong intramolecular helical C-12 and C-15 membered bifurcated hydrogen bonding on both the peptide chains along with propagating the helical architecture of the peptide chains attached. There exists a C-6 hydrogen bonding for the single stranded peptides attached to dimedone. Extensive structural investigations involving single crystal X-ray diffraction, solution-state NMR and CD studies of oligopeptides have been undertaken.
Keywords: dimedone; Helical; hydrogen bonding; Peptides; template

Synthesis of hexaphenylbenzene-based template assembled synthetic proteins - Madhu, Suresh; Madica, Krishnaprasad; Gonnade, Rajesh; Sanjayan, Gangadhar J (Tetrahedron Letters, 2019)
Template-assembled synthetic proteins (TASPs) synthesized from rigid templates have attracted attention due to their interesting structural architectures and potential biomedical applications. Herein, we report the design, synthesis and characterizations of TASPs based on hexaphenylbenzene template (HPB) having twelve peptide attachable axial-arms in its structure. The peptides were attached to all the axial-arms of the template in a single step using simple solution phase peptide coupling strategy. The reaction conditions were standardized systematically using simple amines from smaller size to larger ones. (C) 2019 Elsevier Ltd. All rights reserved.

Structural and computational investigation of an imine-based propeller-shaped macrocyclic cage - Madhu, Suresh; Raghavan, Sriram (SN Applied Sciences, 2021)
In this study, we present the synthesis, spectroscopic and structural characterization of self-assembling gem-dimethyl imine based molecular cage (IMC). Self-assembling macrocycles and cages have well-defined cavities and have extensive functionalities ranging from energy storage, liquid crystals, and catalysts to water splitting photo absorber. IMC has large voids i.e., 25% of the total crystal volume thus could accommodate wide substrates. The synthesized imine-based molecular cages are stabilized by coaxial π bonded networks and long-range periodic van der Waal and non-bonded contacts as observed from the crystal structure. IMC also has typical properties of soft condensed matter materials, hence theoretical prediction of stress and strain tensor along with thermophysical properties were computed on crystal system and were found to be stable. Molecular dynamics revealed IMC is stabilized by, strong interactions between the interstitial phenyl rings. Density functional theory (DFT) based physicochemical properties were evaluated and has band gap of around 2.38ev (520 nm) similar to various photocatalytic band gap materials.